2009
DOI: 10.1016/j.bbmt.2009.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Measured Creatinine Clearance versus Calculated Glomerular Filtration Rate for Assessment of Renal Function before Autologous and Allogeneic BMT

Abstract: Common blood and marrow transplantation (BMT) eligibility criteria include a minimum glomerular filtration rate (GFR) that may vary by regimen intensity. GFR is often estimated by measurement of creatinine clearance in a 24-hour urine collection (24-hr CrCl), an inconvenient and error-prone method that overestimates GFR. The study objectives were to determine which of 6 GFR calculations: Cockroft-Gault (CG), modified CG (mCG), Modification of Diet in Renal Disease 1 (MDRD1), MDRD2, Jelliffe, and Wright, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…This is not surprising since it is the only equation estimating creatinine clearance and not GFR. Although a previous study shares our observation [19], other studies, comparing the CG estimates to GFR, measured with isotope, found poorer performance of CG compared to other equations [18,22,23]. The MDRD equation did worse in mimicking ECC in our study.…”
Section: Estimation Of Renal Functioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This is not surprising since it is the only equation estimating creatinine clearance and not GFR. Although a previous study shares our observation [19], other studies, comparing the CG estimates to GFR, measured with isotope, found poorer performance of CG compared to other equations [18,22,23]. The MDRD equation did worse in mimicking ECC in our study.…”
Section: Estimation Of Renal Functioncontrasting
confidence: 54%
“…As reported in previous studies, all overestimated renal function at lower ranges of ECC and underestimated it at higher ranges [19][20][21][22]. Especially in patients with poor renal function, inaccuracies of the used equations (MPE ranging from 21% for CG and 44% for CKD-EPI equation in the ECC range below 50 mL/(min × 1.73 m 2 ), data not shown) can misguide clinical decisions with important implications for patient care; special attention is required in these patients.…”
Section: Estimation Of Renal Functionmentioning
confidence: 51%
“…Although numerous methods for predicting GFR exist, studies have demonstrated that CrCl measured by the Cockcroft-Gault equation provides reasonable estimates of GFR. 26 A large study of 973 patients found that estimates of renal function using the Cockcroft-Gault method were in general agreement with estimates using the newer Modification of Diet in Renal Disease method. 27 Furthermore, the Cockcroft-Gault equation was developed to predict CrCl rather than GFR, and its accuracy has been evaluated in numerous studies.…”
Section: Discussionmentioning
confidence: 84%
“…27 Furthermore, the Cockcroft-Gault equation was developed to predict CrCl rather than GFR, and its accuracy has been evaluated in numerous studies. [26][27][28][29][30] Another potential limitation is the differences in the measurement of renal function between Japan and all other countries; however, only 14% of all patients in the ITT population were from Japan. 13 Thus, the outcomes observed in this analysis were not likely to be affected by this.…”
Section: Discussionmentioning
confidence: 99%
“…Hazar et al (33) found no correlation between the estimating equations and their radiolabeled GFR measurement. Other studies in the HCT population have assessed whether estimating equations correlate with 24-hour urine collection for Cr clearance (34).…”
Section: Discussionmentioning
confidence: 99%